City Diagnostic Report for City Development Strategy : Kathmandu Metropolitan City - Kathmandu Metropolitan City (World Bank, Kathmandu, 2014)
In conformity with its objective of functioning as a local Government, Kathmandu Metropolitan City (KMC) sought the assistance of the World Bank for the preparation of a City Development Strategy (CDS). The various sectoral as well as integrated strategies presented in this document seem to be an overwhelming demand on KMC with its limited manpower and money. A CDS is essential if KMC is to focus its development potential. The optimism lies in political leadership, enabling environment and necessary support that will be rendered to KMC from civil society. The vision for Kathmandu stresses the need to develop the valley as administrative, cultural and tourism center. The strategy to move towards that vision through improvement in the overall situation of the KMC, however, is likely to be a long drawn struggle, yet achievable. The urban planning study strongly recommends that Kathmandu should be accorded special status as a capital city and large polluting and manufacturing industries should be discouraged immediately and if possible, re-location plans be drawn for existing industries in the near future. Alternatively, service and light industries should be promoted to replace the economic opportunities. Urban areas in KMC are not designated by a functional and occupational structure or contiguity criteria for managing housing and squatter settlements. Housing problems are a serious challenge in a situation where a historically planned city is fast transforming itself into a trade-cum-service center. On the other hand, it is encouraging to note that despite the absence of city specific policies and programs for housing, slums and squatters, the communities are highly organized and are gradually improving their conditions at their own costs, which show their potential for mobilization in participatory home improvement programs.